Pengaruh Good Corporate Governance dan Koneksi Politik terhadap Manajemen Laba - Yanuardi Saputra; Fitra Dharma (Journal on Education, 2024)
The aim of this research is to find out how good company management and political connections impact real earnings management. The indicators of good corporate governance in this research are managerial ownership, institutional ownership, and audit expertise committee. On the other hand, political connections in this research consist of the board of directors and board of commissioners who are connected to politics. This study applies multiple linear regression analysis. In this research, documentation is a data collection method. The data used in this research was obtained from the annual and financial reports of mining companies listed on the Indonesia Stock Exchange from 2018 to 2022. The research results show that all independent variables in this research influence the real earnings management variable simultaneously. The managerial ownership and institutional ownership variables partially influence the real earnings management variable, while the audit committee, politically connected board of commissioners and politically connected board of directors variables do not influence the real earnings management variable.